Data Security Breaches and Privacy in Europe - Wong, Rebecca; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
Data Security Breaches and Privacy in Europe aims to consider data protection and cybersecurity issues; more specifically, it aims to provide a fruitful discussion on data security breaches. A detailed analysis of the European Data Protection framework will be examined. In particular, the Data Protection Directive 95/45/EC, the Directive on Privacy and Electronic Communications and the proposed changes under the Data Protection Regulation (data breach notifications) and its implications are considered. This is followed by an examination of the Directive on Attacks against information systems and a discussion of the proposed Cybersecurity Directive, considering its shortcomings and its effects. The author concludes by looking at whether a balance can be drawn by the current and proposed Data Protection framework to protect against data security breaches and considers what more needs to be achieved.
Foreword -- Introduction -- Data Protection Directive 95/46/EC -- The Amended Directive on Privacy and Electronic Communications -- Art. 29 Working Party: Future of Privacy -- European Commission Communication Opinion 2010 -- Proposed Data Protection Regulation 2012: Data Security Breach Notifications -- Framework Decision 2005/222/JHA and the Directive against Information Systems -- European Data Protection Supervisor’s Opinion on Cybersecurity -- Cybersecurity Directive 2013 -- Criticism of the Cybersecurity Directive -- Concluding Remarks. .
Keywords: Computers and civilization; Mass media; Law; Criminology; Computers and Society; IT Law, Media Law, Intellectual Property; Criminology and Criminal Justice, general